2000
DOI: 10.1021/ma000746h
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/Polymer Inclusion Compounds as a Novel Approach To Obtaining a PLLA/PCL Intimately Compatible Blend

Abstract: Introduction. Aliphatic polyesters represent an important family of biodegradable materials. Increasing attention has been focused on hydrolytically unstable lactone polymers owing to their usefulness in biomedical applications.To enhance the rate of biodegradation, the permeability and the tensile properties of the biomaterials, copolymerization, and blending processes have been used. Blending with other biodegradable polymers might offer a more cost-effective way of modifying the properties of hard and britt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 19 publications
4
141
0
1
Order By: Relevance
“…13). The rapid solidification of PCL and PLLA upon coalescence [12] implies a potentially improved dispersion of the drug in the PCL and PLLA matrices, which likely will critically impact their ability to deliver drugs.…”
Section: Pcl and Plla [27]mentioning
confidence: 99%
“…13). The rapid solidification of PCL and PLLA upon coalescence [12] implies a potentially improved dispersion of the drug in the PCL and PLLA matrices, which likely will critically impact their ability to deliver drugs.…”
Section: Pcl and Plla [27]mentioning
confidence: 99%
“…[1][2][3][4][5] As a non-biodegradable but biocompatible polymer, PEG has been used for many clinical applications. 6 PEG presents outstanding properties, such as hydrophilicity, solubility in water and in organic solvents, nontoxicity, and absence of antigenicity and immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, various synthetic methods have been developed to prepare a variety of PLA/PEG related copolymers with different structures and compositions. These copolymers can be classified according to their block structure as diblock, 5 triblock,…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since Harada et al found that many a-CDs can thread onto a poly(ethylene glycol) (PEG) chain to form a crystalline inclusion complex (IC), [2] it has been found that CDs form ICs with several biodegradable aliphatic polymers, such as PCL, [3] poly(3-hydroxybutyrate), [4] poly(butylene succinate), [5] and their copolymers. [6][7][8] The formation [9,10] and properties of CD-ICs with various polymers have been studied to improve miscibility, [11][12][13] biodegradation, [14] and crystallization of polymers. [15] By threading a-CD molecules, some physical properties of the polymers are changed.…”
Section: Introductionmentioning
confidence: 99%